Analisis Penggunaan Bahasa Jepang sebagai Bahasa Pengantar pada Kursus Intensif Bahasa Jepang - Zaenal Abidin (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
The results of this study discuss the implementation of the Intensive Japanese Language Course held at the Language Education and Training Center of the Ministry of Defense in the 2023 Fiscal Year using the main language of instruction, namely Japanese. This course aims to provide participants with an in-depth understanding of Japanese, especially in a military context. The research method used is library research, which involves collecting data from various sources, including documents, e-journals, and previous research results. The data obtained is then analyzed and reconstructed to provide a clear picture of the learning process and outcomes in this course. In this study, several challenges in the teaching and learning process of the intensive course were identified, especially in the use of Japanese as the language of instruction. Some of the challenges faced include the difficulty of participants in understanding complex sentence structures, limitations in vocabulary, and the level of difficulty in memorizing kanji characters needed for basic Japanese. In addition, challenges in delivering conversational material are also a focus of attention, considering that speaking skills are very important in communicating effectively in Japanese. This study concludes that the Intensive Japanese Language Course for the 2023 Fiscal Year has succeeded in achieving its learning objectives, namely improving participants' competence in basic Japanese. However, there are some recommendations for future improvements, such as updating the curriculum to better suit the needs of participants, improving learning methods that support understanding everyday conversations, and providing more time to enrich vocabulary and deepen understanding of kanji characters. This is expected to help participants achieve higher competency in basic Japanese and support their tasks in work environments that require these language skills.